The economic determinants of U.S. presidential approval: A survey - Michael Berlemann; Sören Enkelmann (Center for Economic Studies and ifo Institute (CESifo), 2012)
Even after four decades of research it remains unclear, whether presidential popularity depends on the state of the economy. While about half of all studies for the United States find a significant effect of unemployment and inflation on presidential popularity, the others do not. Additional economic issues have rarely been studied. In this survey article we study the likely causes for the inconclusive findings. While various factors have an influence on the results, especially the choice of the sample period is of crucial importance. While in the very long run we find unemployment, inflation and the budget deficit to have a robust effect on presidential approval, this holds not true for shorter sub-periods. This result might indicate that the popularity function is instable over time. However, the findings might also be taken as an indication that the most often employed linear estimation approach is inadequate. Further research on these issues is necessary.
Keywords: D72; H11; 330; presidential popularity; approval; unemployment; inflation; Staatsoberhaupt; Öffentliche Meinung; Wirtschaftslage; Arbeitslosigkeit; Inflation; USA